Development of Somatic Embryo in Lithospermum erythrorhizon Siebb. et Zucc and The Study on The Effect of Methyl Jasmonate on its Maturation - Mariani, Totik Sri; Ramayanti, Octavia; Yazaki, Kazufumi; Miyake, Hiroshi (BRIN, 2004)
A research on the somatic embryogenesis in Lithospermum erythrorhizon has been conducted. Embryogenic callus was inoculated in EIM9 liquid medium (modification of LS medium), i.e. L2PVP (initiation medium) and the development of somatic embryo was observed. Ten uM and 100 uM methyl jasmonate was added into L3PVP medium (differentiation medium) for somatic embryo maturation. The purposes of this research were to observe the development of somatic embryo and to observe the effect of methyl jasmonate on maturation of the somatic embryo in L. erythrorhizon. The results showed that somatic embryogenesis in L. erythrorhizon derived from single cells differentiated further forming proembryo, globular heart, torpedo and cotyledon stage. Treatment with 10 uM and 100 uM methyl jasmonate induced maturation of somatic embryos (cotyledon stage) after transferring them to embryo development medium (L4PVP).